Defects in skin γδ T cell function contribute to delayed wound repair in rapamycin-treated mice - Mills, Robyn E. (2008)
Disruptions in the normal program of tissue repair can result in poor wound healing, which perturbs the integrity of barrier tissues such as the skin. Such defects in wound repair occur in transplant recipients treated with the immunosuppressant drug rapamycin (sirolimus). Intraepithelial lymphocytes, such as γδT cells in the skin, mediate tissue repair through the production of cytokines and growth factors. The capacity of skin-resident T cells to function during rapamycin treatment was analyzed in a mouse model of wound repair. Rapamycin treatment renders skin γδ T cells unable to proliferate, migrate and produce normal levels of growth factors. The observed impairment of skin γδ T cell function is directly related to the inhibitory action of rapamycin on mammalian target of rapamycin (mTOR). Skin γδ T cells treated with rapamycin are refractory to IL-2 stimulation and attempt to survive in the absence of cytokine and growth factor signaling by undergoing autophagy. Normal wound closure can be restored in rapamycin-treated mice by addition of the skin γδ T cell-produced factor, insulin-like growth factor-1. These studies not only reveal that mTOR is a master regulator of γδ T cell function but also provide a novel mechanism for the increased susceptibility to nonhealing wounds that occurs during rapamycin administration. This is an author-produced version of a manuscript accepted for publication in The Journal of Immunology (The JI). The American Association of Immunologists, Inc. (AAI), publisher of The JI, holds the copyright to this manuscript. This version of the manuscript has not yet been copyedited or subjected to editorial proofreading by The JI; hence, it may differ from the final version published in The JI (online and in print). AAI (The JI) is not liable for errors or omissions in this author-produced version of the manuscript or in any version derived from it by the U.S. National Institutes of Health or any other third party. The final, citable version of record can be found at www.jimmunol.org.